HERMENEUTIC INTERPRETATION OF THE HADITH ON ONE INTESTINE AND SEVEN INTESTINES: AN ETHICAL PERSPECTIVE ON CONSUMPTION IN ISLAM - Muhamad Maimun; Helmi; Ahmad Fawaid (DAAR EL-KAMIL: Multidisciplinary Journal, 2025)
This study discusses the phenomenon of Musykil al-Ḥadīth (hadiths that appear contradictory or are difficult to understand textually) concerning the difference in eating patterns between believers and disbelievers, symbolized by the expressions “one intestine” and “seven intestines.” Through a hermeneutical approach grounded in classical Islamic scholarship, this article explains that such wording functions as a metaphor for zuhd (asceticism) and self-restraint. The findings indicate that the essence of this hadith is an injunction toward qana’ah (contentment) and a warning against the harmful effects of greed on both physical and spiritual health. To uncover the intended meaning of the hadith, this research employs a hermeneutical method by referring to the sharḥ (commentaries) of prominent scholars. Ibn Ḥajar al-‘Asqalānī emphasizes that the expression should not be understood literally (biologically), but rather as a tamsīl (figurative illustration). Imam al-Nawawī explains that the hadith serves as motivation to minimize excessive attachment to worldly pleasures. Meanwhile, Ibn ‘Abd al-Barr views the hadith as praise for believers who are able to restrain their worldly desires. The core of this study concludes that “one intestine” represents the values of zuhd and qana’ah. A believer is expected to take sustenance only as needed, whether in food, clothing, or work. The fundamental principle is “eating to live” in order to maintain strength for worship, rather than “living to eat” to satisfy desire. Contentment (qana’ah) is thus regarded as a key to success for a Muslim. The research also examines the sociological and health impacts of excessive consumption (greed). Based on the studied materials on consumption ethics, Islam regulates that the stomach should not be filled completely; the ideal division is one-third for food, one-third for drink, and one-third for breathing. Regarding spiritual and physical impacts, excessive satiety, according to Imam al-Shāfi‘ī, can harden the heart, diminish intelligence, cause lethargy, and weaken enthusiasm for worship.